Tick salivary gland proteins (SALPs) as antigens for vaccine development to decrease spirochete load in a murine model of lyme borreliosis - Ullmann-Moore, Amy J., author; Foy, Brian D., advisor; Zeidner, Nordin S., advisor; Piesman, Joseph, committee member; Chisholm, Stephen T., committee member (Colorado State University. Libraries, 2011)
Lyme disease, caused by Borrelia burgdorferi, is the most common tick-borne illness in the United States and selected regions of Eurasia. Members of the Ixodes ricinus complex of ticks are the vectors for B. burgdorferi, with I. scapularis being the primary vector in North America. Lyme disease occurs along the east coast as well as the upper Midwest, with the majority of cases occurring in the northeastern regions of the United States. The number of cases of Lyme disease in the U.S. has increased over the last 20 years with 28,921 cases reported in 2008. Prevention of Lyme disease for humans is currently focused on use of repellants and tick removal, and there is currently no vaccine available. The goal of this dissertation is to test the hypothesis that vaccinating mice with highly immunomodulatory tick salivary proteins in a context that shifts the immune response of the host from a Th2 polarized response, which is normal for tick feeding (Ferreira and Silva 1999), to a Th1 response would block transmission of B. burgdorferi by infected ticks. To these ends the objectives of this research were to: 1) Generate adenoviral vaccine vectors containing the tick salivary gene of interest to drive the Th1 response (Chapter 2), 2) test the adenovirus constructs in a murine model for their ability to induce a Th1 shift in cytokines and a subsequent reduction or block of tick-transmitted B. burgdorferi infection (Chapter 3), and 3) identify more potential tick salivary genes for vaccine antigens utilizing DNA vaccine methodology. Tick saliva contains a wide range of physiologically active molecules that are critical for effective attachment and engorgement of the tick. While taking a blood meal, hard ticks attach to their vertebrate hosts for several days and introduce saliva, together with pathogens into the skin. During this period, it is necessary for the tick to enhance blood flow, circumvent the host immune response and prevent healing of the feeding site to continue to imbibe blood from the feeding pool created by the tick. It has been demonstrated that immunizing the host with molecules from tick saliva can negatively affect not only tick feeding, but pathogen transmission as well, thereby protecting the host from pathogen transmission. Seven molecules from I. scapularis were investigated in either an adenoviral vaccine vector or in a DNA vaccine vector for their ability to block tick-transmitted B. burgdorferi infection in a murine model. Complete prevention of transmission was not observed, but a 60% reduction of spirochete load was observed using a combination of molecules in an adenoviral vector.
Keywords: anti-tick vaccine; Ixodes; Borrelia